2021
DOI: 10.1123/ijspp.2019-0910
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Dorsolateral Prefrontal Cortex High-Definition Transcranial Direct-Current Stimulation Improves Time-Trial Performance in Elite Cyclists

Abstract: Background: The effects of anodal transcranial direct-current stimulation (tDCS) on endurance exercise performance are not yet fully understood. Different stimulated areas and low focality of classical tDCS technique may have led to discordant results. Purpose: This study investigated the effect of a bilateral anodal high-definition tDCS (HD-tDCS) of the dorsolateral prefrontal cortex on the cycling time-trial (TT) performance and physiological and perceptual response at moderate intensity in elite cyclists. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 37 publications
2
29
1
Order By: Relevance
“…Nonetheless, Pollastri et al 46 recently demonstrated a 1.3% faster 15 km time-trial in eight elite cyclists after bilateral HD-tDCS over the DLPFC (F3 and F4) with 1.5 mA for 20 min. As previously mentioned, the performance improvement shown by Pollastri et al 46 , despite seeming small may represent an important advantage considering the high level of performance of the sample 55 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Nonetheless, Pollastri et al 46 recently demonstrated a 1.3% faster 15 km time-trial in eight elite cyclists after bilateral HD-tDCS over the DLPFC (F3 and F4) with 1.5 mA for 20 min. As previously mentioned, the performance improvement shown by Pollastri et al 46 , despite seeming small may represent an important advantage considering the high level of performance of the sample 55 .…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, Pollastri et al 46 recently demonstrated a 1.3% faster 15 km time-trial in eight elite cyclists after bilateral HD-tDCS over the DLPFC (F3 and F4) with 1.5 mA for 20 min. As previously mentioned, the performance improvement shown by Pollastri et al 46 , despite seeming small may represent an important advantage considering the high level of performance of the sample 55 . The difference between the present study and the study by Pollastri et al 46 may be explained by the different areas of stimulation, as HD-tDCS was applied over M1 in the present study and over the DLPFC in their study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations